A review of antibiotic resistance in Group B Streptococcus: the story so far. (3rd May 2020) - Hayes, Katherine; O'Halloran, Fiona; Cotter, Lesley
Abstract: Group B Streptococcus (GBS) is the leading cause of neonatal disease worldwide, and invasive disease in adults is becoming more prevalent. Currently, some countries adopt an intrapartum antibiotic prophylaxis regime to help prevent the transmission of GBS from mother to neonate during delivery. This precaution has reduced the incidence of GBS-associated early-onset disease; however, rates of late-onset disease and stillbirths associated with GBS infections remain unchanged. GBS is still recognized as being universally susceptible to beta-lactam antibiotics; however, there have been reports of reduced susceptibility to beta-lactams, including penicillin, in some countries. Resistance to second-line antibiotics, such as erythromycin and clindamycin, remains high amongst GBS, with several countries noting increased resistance rates in recent years. Moreover, resistance to other antibiotic classes, such as fluoroquinolones and aminoglycosides, also continues to rise. In instances where patients are allergic to penicillin and second-line antibiotics are ineffective, vancomycin is administered. While vancomycin, a last resort antibiotic, still remains largely effective, there have been two documented cases of vancomycin resistance in GBS. This review provides a comprehensive analysis of the prevalence of antibiotic resistance in GBS and outlines the specific resistance mechanisms identified in GBS isolates to date.